Salina: the story of a "noble" prostitute - Abdul Rani, Mohd Zariat (Dewan Bahasa dan Pustaka, 2009)
The argument in this article stems from A. Samad Said's statement that his first novel, Salina, revolves around every character in the novel, as opposed to being focused on the character Siti Salina alone. His statement is contentious, because it visibly contradicts the conclusions made in numerous articles and studies on Salina. Generally, these articles and studies find Salina's plot to centre on the protagonist Siti Salina, a 'noble prostitute' who lives in Singapore during World War Two. Because of this focus, the presence of Siti Salina is the cause of a lingering controversy. To frame this dispute, this article analyses the narrative devices in Salina, to identify the focus of the story, so as to confirm Samad's statement above. These include the characters and their characteristics, the geographical and chronological backdrop, plot (especially with regard to cause and effect), as well as the scenes and their description, including the manipulation of language. The analysis identifies two narrative strategies manipulated together in Salina, that simultaneously highlight her nobility and downplay her transgressions; both of which focus the story on the noble prostitute. This finding in itself negates the validity of A. Samad Said's statement above, and conversely reaffirms the findings previous articles and studies.